2007
DOI: 10.1073/pnas.0703832104
|View full text |Cite
|
Sign up to set email alerts
|

Linking folding with aggregation in Alzheimer's β-amyloid peptides

Abstract: Growing evidence suggests that the ␤-amyloid (A␤) peptides of Alzheimer's disease are generated in early endosomes and that small oligomers are the principal toxic species. We sought to understand whether and how the solution pH, which is more acidic in endosomes than the extracellular environment, affects the conformational processes of A␤. Using constant pH molecular dynamics simulations of two model peptides, A␤(1-28) and A␤(10 -42), we found that the folding landscape of A␤ is strongly modulated by pH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
202
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(220 citation statements)
references
References 53 publications
16
202
0
Order By: Relevance
“…It was further suggested that small A␤ oligomers may form intracellularly before being released into the extracellular medium, in which they may interfere with synaptic activity or act as seeds to accelerate fibril formation (Selkoe, 2004;Khandogin and Brooks, 2007). Thus, preventing or reversing the formation of aggregated amyloid would appear to be a promising strategy for AD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It was further suggested that small A␤ oligomers may form intracellularly before being released into the extracellular medium, in which they may interfere with synaptic activity or act as seeds to accelerate fibril formation (Selkoe, 2004;Khandogin and Brooks, 2007). Thus, preventing or reversing the formation of aggregated amyloid would appear to be a promising strategy for AD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Among these methods, the continuous pH molecular dynamics (pHMD) method 7,8 based on λ dynamics, 9 which will be referred to as CpHMD hereafter, has been successfully applied to pK a predictions 10 and pH-dependent protein folding 11 and conformational dynamics. 12,13 The first version of the CpHMD technique makes use of the generalized Born (GB) implicit-solvent model for propagating both conformational and titration coordinates and the temperature-based a) Present address: Department of Pharmaceutical Sciences, University of Maryland, Baltimore, Maryland 21201, USA. E-mail: jshen@rx.umaryland.edu.…”
Section: Introductionmentioning
confidence: 99%
“…This observation, together with more efficient pKa prediction methods (e.g. [73]) and the emergence of constant pH molecular dynamics simulations [74][75][76][77][78][79][80] to model the protonation-dependent structural changes will spark more experimental and theoretical work in pH effects on protein-protein binding.…”
Section: Influence Of Phmentioning
confidence: 99%